Possibilities of Mobile Applications to Improve the Quality of Education - Farmonova Madina Azamovna (International Journal on Orange Technologies, 2021)
The introduction of mobile technology in the educational process is the most promising method of teaching, the most useful method of teaching in the traditional educational process, the introduction of new forms of teaching in the traditional educational process introduction